PENGARUH LATIHAN DENGAN MEDIA TONGKAT TARGET TERHADAP TEKNIK DASAR BLOK BOLA VOLI DI SMA - Putra, Adhitya Kharisma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Abstract The problem in this research is there any influence of media practice with the target stick to the basic techniques of volleyball at SMAK block Abdi Discourse Pontianak. The purpose of this study to determine the effect of exercise with targeted media stick to the basic techniques of volleyball block.The method used in this research is quantitative method with type research exsperimental true design and design using pretest-posttest control group design. Use the entire student population of men who follow extracurricular volleyball of 20 people. The research sample using simple random sampling technique with 10 students as control class and experimental class of 10 students to follow extracurricular volleyball. Data analysis was performed using t-test.Results of the research were obtained an average result block students' extracurricular at the initial test control class 20.2 and the average test end 23.5 with the difference or the amount of an increase of 3.3 while the experimental class of initial tests 19.6 and the average test end 27.9 with the difference or increase from the 8.3. The value of the post-test experimental class and control class with significant value 0.033> 0.05 so that the alternative hypothesis is accepted that there are significant media workout with the target stick to the basic techniques of block. The percentage of increase is 42.3%. Keywords: Target Stick Media, Block, Volleyball.